Electromagnetic Interference Shielding: Electromagnetic Shielding of Monolayer MXene Assemblies (Adv. Mater. 9/2020). Issue 9 (3rd March 2020) - Yun, Taeyeong; Kim, Hyerim; Iqbal, Aamir; Cho, Yong Soo; Lee, Gang San; Kim, Myung‐Ki; Kim, Seon Joon; Kim, Daesin; Gogotsi, Yury; Kim, Sang Ouk; Koo, Chong Min
Abstract : In article number 1906769, Yury Gogotsi, Sang Ouk Kim, Chong Min Koo, and co‐workers report systematic experimental and theoretical exploration of the electromagnetic interference (EMI) shielding behavior of two‐dimensional Ti3 C2 T x MXene assembled films over a broad range of film thicknesses, monolayer by monolayer. A monolayer assembled film offers ≈20% shielding of electromagnetic waves, while a 55 nm thickness demonstrates 99% shielding, revealing that MXene is the best candidate for lightweight EMI shielding applications.